FELINE AORTIC THROMBOEMBOLISM: CASE REPORT - Figueroa A., Lizbeth (2014)
A case of a 13 year old Siamese cat whit feline aortic thromboembolism is presented. This is a devastating complication associated to hypertrophic cardiomyopathy (HCM), one of the most common heart disease in cats characterized by a significant left concentric ventricular hypertrophy.